Under the wave at Waimea [compact disc, unabridged] - Theroux, Paul (Houghton Mifflin Harcourt, 2021)
Now in his sixties, big-wave surfer Joe Sharkey has passed his prime. The younger surfers around the breaks on the north shore of Oahu still idolize the Shark, but his sponsors are looking elsewhere. After one too many drinks, Joe accidentally kills a stranger near Waimea, a tragedy that sends his life out of control. Joe's devoted girlfriend, Olive, throws herself into uncovering the dead man's identity and helping Joe find vitality and refuge in the waves again.